Application of a Schizosaccharomyces pombe Edc1-fused Dcp1–Dcp2 decapping enzyme for transcription start site mapping - Paquette, David R. (RNA, 2018)
Changes in the 5′ leader of an mRNA can have profound effects on its translational efficiency with little effect on abundance. Sequencing-based methods to accurately map the 5′ leader by identifying the first transcribed nucleotide rely on enzymatic removal of the 5′ eukaryotic cap structure by tobacco acid pyrophosphatase (TAP). However, commercial TAP production has been problematic and has now been discontinued. RppH, a bacterial enzyme that can also cleave the 5′ cap, and Cap-Clip, a plant-derived enzyme, have been marketed as TAP replacements. We have engineered a Schizosaccharomyces pombe Edc1-fused Dcp1–Dcp2 decapping enzyme that functions as a superior TAP replacement. It can be purified from E. coli overexpression in high yields using standard biochemical methods. This constitutively active enzyme is four orders of magnitude more catalytically efficient than RppH at 5′ cap removal, compares favorably to Cap-Clip, and the 5′ monophosphorylated RNA product is suitable for standard RNA cloning methods. This engineered enzyme is a better replacement for TAP treatment than the current marketed use of RppH and can be produced cost-effectively in a general laboratory setting, unlike Cap-Clip.